Hygienic status of fresh non ripened sausages (Home type sausages) in the region of Thessalia - ΠΑΠΑΝΑΣΤΑΣΙΟΥ, Κ.; ΜΟΥΤΛΙΑ, XP.; ΔΕΣΠΟΤΟΠΟΥΛΟΥ, Α.; ΜΑΓΚΟΥΤΑ, Π. (Journal of the Hellenic Veterinary Medical Society, 2019)
We examined microbiologically 110 samples offresti non ripened sausages (home made type sausages) of different sausage factories in the region of Thessalia in order to determine the hygienic status and demonstrate the acceptability or not of them. The examination proved that the hygienic status of the sampled sausages is not satisfactory and measures are proposed in order to make these products safer for the consumer